FACTORS OF SEMANTIC EMOTION OF COVID-19 NEWS AFTER INTRODUCTORY VACCINE ON TWITTER - Friska . Pakpahan; Anni Holila Pulungan; Meisuri . Meisuri (LINGUISTIK TERAPAN, 2022)
This study is based on the fact that the readers get words emotion after reading the tweets of covid-19 news. Various emotions found on the tweets of twitter relate to the Covid-19 news. Some of them make the readers being fear or sad of this pandemic. This study deals with semantic emotion of covid-19 news in twitter account of CNN Breaking News. The objectives of the study is to investigate how the semantic emotions realized in Covid-19 news. The study was conducted by using descriptive qualitative. The data of this study were words from tweets which contain semantic emotion of Covid-19 news in twitter. The sources of data in this study were Covid-19 news in twitter, after vaccine Covid-19 distributed since beginning of January 2021. It was found that emotions were realized in covid-19 news, namely: basic emotion, emotional relations, caused emotions, causative, emotional goals, and complex emotions. Contrary with the expectation, happiness was the dominant emotion found in covid-19 news on twitter. Happiness is an emotion to show pleasant, while covid-19 in unpleasant situation. But in this research, it was found that happiness had a high frequency.Keywords: Semantic Emotion, Covid-19, Twitter, Vaccine